2017
DOI: 10.1002/pssa.201600688
|View full text |Cite
|
Sign up to set email alerts
|

Solar blind photodetector based on epitaxial zinc doped Ga2O3 thin film

Abstract: We report on the fabrication and characterization of solar blind photodetectors (SBPs) based on undoped β‐Ga2O3 and Zn doped (∼5 × 1020 cm−3) β‐Ga2O3 (ZnGaO) epitaxial films with cutoff wavelength of ∼260 nm. The epilayers were grown on c‐sapphire by the metal organic chemical vapor deposition technique and their structural, electrical and optical properties were characterized using various methods. As grown films have a large number of defects, resulting in detectors with enhanced internal gain, hence, high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 39 publications
1
57
0
Order By: Relevance
“…It was worthy to mention that the responsivity for the annealed ZnGa 2 O 4 PDs devices dropped significantly (Fig. 5(c)), which is consistent to those reported in earlier studies 12,22 . Even though, the selectivity of the DUV PDs made of ZnGa 2 O 4 annealed at 800 °C presents the highest for these DUV PDs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It was worthy to mention that the responsivity for the annealed ZnGa 2 O 4 PDs devices dropped significantly (Fig. 5(c)), which is consistent to those reported in earlier studies 12,22 . Even though, the selectivity of the DUV PDs made of ZnGa 2 O 4 annealed at 800 °C presents the highest for these DUV PDs.…”
Section: Resultssupporting
confidence: 90%
“…The calculated carrier concentration, mobility, and resistivity of the ZnGa 2 O 4 films were 6.72 × 10 16  cm −3 , 1.4 cm 2 /Vs, and 67.9 Ω-cm, respectively. These values indicate that ZnGa 2 O 4 films are promising for several optoelectronic applications 12 . In this work, the solar-blind PDs made of the ZnGa 2 O 4 epilayers grown by MOCVD were studied.…”
Section: Introductionmentioning
confidence: 89%
“…Due to this, the 2.6 eV band was considered a signature emission of the acceptor levels. Furthermore, Alema et al have also shown very recently that a band centered at 2.7 eV, is strongly influenced by the presence of Zn and specifically assigned it to recombination between V O donors and Zn Ga acceptors. Besides, a similar band around 480 nm (2.6 eV) was observed in Mn‐doped Ga 2 O 3 and tentatively assigned to levels related to the presence of Mn, which is usually in the Mn 2+ ionization state and would therefore result in p‐type doping .…”
Section: Resultsmentioning
confidence: 97%
“…Gallium oxide has been shown to be a promising candidate for a wide variety of devices, including field‐effect transistors (FETs), Schottky barrier diodes, and UV photodetectors . The monoclinic form (β‐gallium oxide [β‐Ga 2 O 3 ]) of gallium oxide has been subjected to intensive research interests recently because of its thermal and chemical stabilities .…”
Section: Introductionmentioning
confidence: 99%